Synergy among thymol, eugenol, berberine, cinnamaldehyde and streptomycin against planktonic and biofilm‐associated food‐borne pathogens. (1st May 2015) - Liu, Q.; Niu, H.; Zhang, W.; Mu, H.; Sun, C.; Duan, J.
Abstract : Abstract: Essential oils have been found to exert antibacterial, antifungal, spasmolytic, and antiplasmodial activity and therapeutic effect in cancer treatment. In this study, the antibacterial activities of four main essential oils' components (thymol (Thy), eugenol (Eug), berberine (Ber), and cinnamaldehyde (Cin)) were evaluated against two food‐borne pathogens, Listeria monocytogenes and Salmonella Typhimurium, either alone or in combination with streptomycin. Checkerboard assay demonstrated that Thy and Cin elicited a synergistic effect with streptomycin against L . monocytogenes, while a synergy existed between Cin or Eug and streptomycin against Salm . Typhimurium. Further experiments showed that this synergy was sufficient to eradicate biofilms formed by these two bacteria. Thus, our data highlighted that the combinations of specific components from essential oils and streptomycin were useful for the treatment of food‐borne pathogens, which might help prevent the spread of antibiotic resistance through improving antibiotic effectiveness. Significance and Impact of the Study: This study has shown the synergistic effect of four components of essential oil (thymol, eugenol, berberine and cinnamaldehyde) combined with streptomycin on planktonic and biofilm‐associated food‐borne pathogens Listeria monocytogenes and Salmonella Typhimurium. These findings indicate that combination of specific components of essential oils with streptomycin may provide alternative methods to overcome the problem of food‐borne bacteria both in suspension and in biofilm.